PENGARUH CONTENT MARKETING, CELEBRITY ENDOSER, LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN ( Studi kasus Situasi Seteleh Penutupan TikTok) - Mayang Eka Oktavia Nardiana; Endah Budiarti (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The research objects are students at the University of 17 August 1945 Surabaya who use the social media Tiktok and who have shopped at the TikTok Shop. This research aims to determine how Content Marketing, Celebrity Endorser, Live Streaming simultaneously influence purchasing decisions after the closure of the TikTok Shop. This research uses quantitative methods. The research sample was 96 respondents using non-probability sampling techniques. Primary data was obtained using a questionnaire while secondary data was obtained using literature study. Data analysis uses instrument tests, classical assumption tests, t tests, F tests, multiple linear regression tests, determination tests. Based on the research results, it shows that content marketing influences purchasing decisions after the closure of the TikTok Shop, celebrity endorsers influence purchasing decisions after the closure of the TikTok Shop, live streaming influences purchasing decisions after the closure of the TikTok Shop, Content Marketing, Celebrity Endorser, Live Streaming simultaneously influence purchase decision after the closure of the TikTok Shop. The determination results of all independent variables (Content Marketing, Celebrity Endorser, Live Streaming) contributed 23.3% to the dependent variable (Purchase Decision) and the remaining 76.7% was influenced by other variables not included in the research